РЕШИТЬ ПОЖАЛУЙСТА СРОЧНО НУЖНО!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!
РЕШИТЬ ПОЖАЛУЙСТА СРОЧНО НУЖНО!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!
Ответ(ы) на вопрос:
1
16*4^x-10*4^x=16
6*4^x=16
4^x=8/3
x=log(4)(8/3)=3/2-log(4)3
2
7^x=a
(a-1)/3=(7a+49)/7a
7a(a-1)=3(7a+49)
7a²-7a-21a-147=0
7a²-28a-147=0
a²-4a-21=0
a1+a2=4 U a1*a2=-21
a1=-3⇒7^x=-3 нет решения
a2=7⇒7^x=7⇒x=1
3
3^x=a
a²-12a+27=0
a1+a2=12 U a1*a2=27
a1=3⇒3^x=3⇒x=1
a2=9⇒36x=9⇒x=2
4
Разделим на 81^x
3(4/9)^2x-5*(4/9)^x)+2=0
(4/9)^x=a
3a²-5a+2=0
D=25-24=1
a1=(5-1)/6=2/3⇒(4/9)^x=2/3⇒x=1/2
a2=(5+1)/6=1⇒(4/9)^x=1⇒x=0
№1
[latex] 2^{2x+4} -10*4^x=2^4[/latex]
[latex] 2^{2x} *2^4-10* 2^{2x} =2^4[/latex]
[latex]2^{2x} (2^4-10) =2^4[/latex]
[latex]2^{2x} *6 =16[/latex]
[latex]2^{2x} *3 =8[/latex]
[latex]2^{2x} = \frac{8}{3} [/latex]
[latex]2x=log_{2} \frac{8}{3} [/latex]
[latex]2x=log_{2} {8} -log_{2} 3[/latex]
[latex]2x=3} -log_{2} 3[/latex]
[latex]x=1.5 - \frac{1}{2} log_{2} 3[/latex]
[latex]x=1.5 - log_{2} \sqrt{3} [/latex]
Ответ: [latex]1.5 - log_{2} \sqrt{3} [/latex]
№2
[latex] \frac{7^x-1}{3} = \frac{ 7^{x+1}+49 }{ 7^{x+1} } [/latex]
[latex]({7^x-1})* 7^{x+1} } =({ 7^{x+1}+49 )*3 [/latex]
[latex] 7^{2x+1} } - 7^{x+1} = 3*7^{x+1}+147[/latex]
[latex] 7^{2x+1} } - 7^{x+1} - 3*7^{x+1}-147=0[/latex]
[latex] 7^{2x+1} } - 4*7^{x+1}-147=0[/latex]
[latex] 7^{2x} }*7 - 4*7*7^{x}-147=0[/latex]
[latex] 7*7^{2x} } - 28*7^{x}-147=0[/latex]
[latex] 7^{2x} } - 4*7^{x}-21=0[/latex]
Замена: [latex]7^x=t,[/latex] [latex]t\ \textgreater \ 0[/latex]
[latex]t^2-4t-21=0[/latex]
[latex]D=(-4)^2-4*1*(-21)=100[/latex]
[latex]t_1= \frac{4+10}{2}=7 [/latex]
[latex]t_2= \frac{4-10}{2}\ \textless \ 0 [/latex]
[latex]7^x=7[/latex]
[latex]x=1[/latex]
Ответ: 1
№ 3
[latex]9^x-12*3^x+27=0[/latex]
[latex] 3^{2x} -12*3^x+27=0[/latex]
Замена: [latex]3^x=t,[/latex] [latex]t\ \textgreater \ 0[/latex]
[latex]t^2-12t+27=0[/latex]
[latex]D=12^2-4*1*27=36[/latex]
[latex]t_1= \frac{12+6}{2}=9 [/latex]
[latex]t_2= \frac{12-6}{2}=3 [/latex]
[latex]3^x=9[/latex] или [latex]3^x=3[/latex]
[latex]x=2[/latex] или [latex]x=1[/latex]
Ответ: 1; 2
№4
[latex]3*16^x+2*81^x=5*36^x[/latex]
[latex]3* 4^{2x} +2* 9^{2x} -5*36^x=0[/latex]
[latex]3* 4^{2x} +2* 9^{2x} -5*4^x*9^x=0[/latex] [latex]|: 9^{2x} [/latex]
[latex]3* ( \frac{4}{9}) ^{2x} +2 -5* ( \frac{4}{9}) ^{x} =0[/latex]
Замена: [latex]( \frac{4}{9}) ^{x}=t, [/latex] [latex] t\ \textgreater \ 0[/latex]
[latex]3t^2-5t+2=0[/latex]
[latex]D=(-5)^2-4*3*2=1[/latex]
[latex]t_1= \frac{5+1}{6} =1[/latex]
[latex]t_2= \frac{5-1}{6} = \frac{2}{3} [/latex]
[latex]( \frac{4}{9})^x = \frac{2}{3} [/latex] или [latex]( \frac{4}{9})^x =1[/latex]
[latex] ( \frac{2}{3})^{2x} = \frac{2}{3} [/latex] или [latex]x=0[/latex]
[latex]{2x} =1[/latex]
[latex]x=0.5[/latex]
Ответ: 0.5; 1
Не нашли ответ?
Похожие вопросы